Impact : women writing after concussion - Morin, E. D. (Elaine D.), 1964-; Cawthorne, Jane (University of Alberta Press, 2021)
"In Impact, 21 women writers consider the ramifications of concussion on their personal and professional lives. The anthology bears witness to the painstaking work that goes into redefining identity and regaining creative practice after a traumatic event. By sharing their complex, non-linear, and sometimes incomplete healing journeys, these women convey the magnitude of a disability which is often doubted, overlooked, and trivialized, in part because of its invisibility. Showcasing a diversity of women's stories, Impact offers compassion and empathy to all readers and families healing from concussion and other types of trauma. Contributors: Adèle Barclay, Jane Cawthorne, Tracy Wai de Boer, Stephanie Everett, Mary-Jo Fetterly, Rayanne Haines, Jane Harris, Kyla Jamieson, Alexis Kienlen, Claire Lacey, E. D. Morin, Julia Nunes, Shelley Pacholok, Chiedza Pasipanodya, Judy Rebick, Julie Sedivy, Dianah Smith, Carrie Snyder, Kinnie Starr, Amy Stuart, Anna Swanson."--